In transgender men (female‐to‐male), are long‐acting testosterone injections an effective masculinizing therapy?. Issue 2 (February 2017) - Fondell, Nathaniel; Feldman, Jamie
Abstract : EVIDENCE‐BASED ANSWER : Yes. Long‐acting testosterone injections are an effective masculinizing therapy as determined by patient satisfaction and time to amenorrhea for transgender men (SOR: B, lower‐quality individual RCT). Long‐acting testosterone injections also increase lean muscle mass, facial hair, and sexual desire (SOR: C, lower‐quality prospective observational studies).